A social semiotic analysis of women’s political self-branding on Instagram in the Indonesian parliament elections - Hendri Pitrio Putra; Nurul Khairani Abduh; Sairil Sairil; Asyrafunnisa Asyrafunnisa; Yohanis Rongre (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study analyzes the construction of political images of women legislative candidates on Instagram in the context of persistently low women's representation in the Indonesian House of Representatives (20.52% in 2019) despite the implementation of a 30% gender quota. The research explores the visual representation strategies employed by women politicians to enhance visibility and electability within a male-dominated political landscape. Employing qualitative methods and a social semiotic approach, this study examines eight Instagram posts from eight women candidates representing eight different political parties who were successfully elected in the 2024 General Election. The analytical framework integrates Kress and van Leeuwen's theory of visual grammar with Barthes' concepts of connotation and cultural myth. The findings reveal that candidates construct self-representations emphasizing closeness to constituents, religious and cultural values, femininity, professionalism, and integrity. The negotiation of visual meaning occurs through hybrid strategies that combine traditional gender roles (motherhood and domesticity) with attributes of modern political leadership, reflecting efforts to meet societal gender expectations while establishing political credibility. Local political dynamics, including the multiparty system and male dominance, shape adaptive and contextual representation strategies in the digital space. This study demonstrates that Instagram functions as a multimodal arena for political communication rich in social, spiritual, ideological, and cultural meanings. The findings contribute theoretical implications for advancing social semiotics and digital political communication studies by emphasizing the contextual and ideological nature of visual meaning. Practical implications include promoting gender-sensitive political communication strategies and strengthening more substantive women's political representation in the digital sphere.